Characterization of naturally occurring autoantibodies against tumour necrosis factor-alpha (TNF-alpha): in vitro function and precise epitope mapping by phage epitope library. - Sioud, M (1994)
Naturally occurring autoantibodies against cytokines exist in the sera of patients with autoimmune diseases as well as in the sera of normal individuals. We report here that affinity-purified autoantibodies against human TNF-alpha from one rheumatoid arthritis (RA) patient inhibited the cytotoxic effect of TNF-alpha on the mouse fibrosarcoma cell line WEHI 164, by 50%. In an attempt to predict the autoantibodies' recognition site on TNF-alpha protein we screened a random nanopeptide phage library with the affinity-purified TNF-alpha autoantibodies. Among 63 random selected clones, 46 clones carried the sequence ASSLLASSP, NSSPYLNTK or PQSPGSSFP. Frequency analysis of the relative occurrence of the 20 amino acids in the nanopeptides displayed by 50 random bacteriophages picked before selection and 63 after selection to bind to TNF-alpha autoantibodies indicated that proline (P < 0.0003) and serine (P < 0.04) are involved in the binding of the autoantibodies to the phages. Furthermore, we demonstrated that three synthetic peptides (ASSLLASSP, NSSPYLNTK and PPLKPVIDE) displayed by the selected phages reduced the binding of the autoantibodies to TNF-alpha protein by 50%. Interestingly, the sera of mice (BALB/c) immunized with phages displaying ASSLLASSP and NSSPYLNTK peptide showed an anti-TNF-alpha response as detected by ELISA. This response was not found in mice immunized with the wild type phage. Thus, the recombinant phages selected from the phage libraries could be used as carrier for immunization, and therefore as a tool for vaccine development. This work sets the stage for experiments designed to isolate ligands for protective antibodies.